Volatile organic compounds of hoary stock are responsible for suppressing downy mildew of grape in an intercropping system - Weiping Deng; Fei Du; Rongliang Yang; Hanyang Yao; Min Yang; Xinyue Mei; Chen Ye; Su Li; Yixiang Liu; Huichuan Huang; Shusheng Zhu (Phytopathology Research)
Abstract Grape downy mildew (Plasmopara viticola) is an air-borne disease and difficult to control. It has been observed that intercropping grapevines (Vitis vinifera) with aromatic plants can effectively suppress the airborne disease and volatile organic compounds (VOCs) from the aromatic plants are believed to have antimicrobial activities. In this study, a two-year field trial was established by intercropping grapevine and hoary stock (Matthiola incana) to evaluate the control of grape downy mildew. The field results showed that intercropping effectively suppressed grape downy mildew, particularly during the blooming stage of hoary stock. VOCs from hoary stock plants exhibited a dosage-dependent antimicrobial activity against grape downy mildew. To examine the role of VOCs, hoary stock plants were grown in an enclosed chamber, and VOCs were collected at the time points before and post blooming. The collected VOCs were subjected to gas chromatography-mass spectrometry (GC–MS) analysis and in vitro bioassays. Twenty-four VOCs found from pre-blooming and 36 VOCs from post-blooming hoary stock plants were identified. Seventeen VOCs demonstrated consistent inhibitory activities against P. viticola, including seven terpenoids, five benzenoids, and five aliphatics. Among the 17 VOCs, five were unique to post-blooming hoary stock, while 12 were common to both pre- and post-blooming hoary stock. The antimicrobial VOCs offers a potential eco-friendly alternative to managing downy mildew.